Modulations of Cardiac Functions and Pathogenesis by Reactive Oxygen Species and Natural Antioxidants - Sun-Hee Woo; Joon-Chul Kim; Nipa Eslenur; Tran Nguyet Trinh; Long Nguyen Hoàng Do (MDPI AG, 2021)
Homeostasis in the level of reactive oxygen species (ROS) in cardiac myocytes plays a critical role in regulating their physiological functions. Disturbance of balance between generation and removal of ROS is a major cause of cardiac myocyte remodeling, dysfunction, and failure. Cardiac myocytes possess several ROS-producing pathways, such as mitochondrial electron transport chain, NADPH oxidases, and nitric oxide synthases, and have endogenous antioxidation mechanisms. Cardiac Ca2+-signaling toolkit proteins, as well as mitochondrial functions, are largely modulated by ROS under physiological and pathological conditions, thereby producing alterations in contraction, membrane conductivity, cell metabolism and cell growth and death. Mechanical stresses under hypertension, post-myocardial infarction, heart failure, and valve diseases are the main causes for stress-induced cardiac remodeling and functional failure, which are associated with ROS-induced pathogenesis. Experimental evidence demonstrates that many cardioprotective natural antioxidants, enriched in foods or herbs, exert beneficial effects on cardiac functions (Ca2+ signal, contractility and rhythm), myocytes remodeling, inflammation and death in pathological hearts. The review may provide knowledge and insight into the modulation of cardiac pathogenesis by ROS and natural antioxidants.